2014
DOI: 10.1021/jm501174m
|View full text |Cite
|
Sign up to set email alerts
|

Novel DNA Gyrase Inhibiting Spiropyrimidinetriones with a Benzisoxazole Scaffold: SAR and in Vivo Characterization

Abstract: The compounds described herein with a spirocyclic architecture fused to a benzisoxazole ring represent a new class of antibacterial agents that operate by inhibition of DNA gyrase as corroborated in an enzyme assay and by the inhibition of precursor thymidine into DNA during cell growth. Activity resided in the configurationally lowest energy (2S,4R,4aR) diastereomer. Highly active compounds against Staphylococcus aureus had sufficiently high solubility, high plasma protein free fraction, and favorable pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 44 publications
2
57
0
Order By: Relevance
“…Strains exist with efflux pumps knocked out either individually or in combination, and the relative contribution of each system to the susceptibility to major classes of antimicrobials has been defined (15). For the most part, tolC is the major contributor to efflux in E. coli, and knockout of this gene is often used to assess whether novel compounds lack cellular activity due to efflux (16)(17)(18)(19)(20)(21)(22)(23)(24). Similarly, mutations in several genesincluding lpxC (25-27), lptD (28, 29), and lptE (30, 31)-leading to increased permeability of E. coli have been described, and strains harboring such lesions are often used to assess the effect of increased cellular penetration on the bioactivity of molecules (32-37).…”
mentioning
confidence: 99%
“…Strains exist with efflux pumps knocked out either individually or in combination, and the relative contribution of each system to the susceptibility to major classes of antimicrobials has been defined (15). For the most part, tolC is the major contributor to efflux in E. coli, and knockout of this gene is often used to assess whether novel compounds lack cellular activity due to efflux (16)(17)(18)(19)(20)(21)(22)(23)(24). Similarly, mutations in several genesincluding lpxC (25-27), lptD (28, 29), and lptE (30, 31)-leading to increased permeability of E. coli have been described, and strains harboring such lesions are often used to assess the effect of increased cellular penetration on the bioactivity of molecules (32-37).…”
mentioning
confidence: 99%
“…Thus, it is expected that AZD0914 should not exhibit significant mechanism-based toxicity in humans. Indeed, AZD0914 showed no in vitro mammalian genotoxicity and no measurable toxicity in an in vivo rat micronucleus assay (21).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several potent inhibitors such as novobiocin, clorobiocin, cyclothialidine, and 5ʹ-adenylyl-β,γ-imidodiphosphate (ATP analog) were found to interact with Asp-73, crucial amino acid present in the ATP binding domain of DNA Gyrase [32]. Basarab et al synthesized spiropyrimidinetriones with a benzisoxazole heterocyclic scaffold and reported that these derivatives possess potent DNA Gyrase inhibitory activity [33]. Literature findings revealed that various oxazolones derivatives exhibit potent antimicrobial activity against Gramnegative and Gram-positive organisms.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%